2018
DOI: 10.1039/c8fo01301b
|View full text |Cite
|
Sign up to set email alerts
|

Lycopene attenuates AFB1-induced renal injury with the activation of the Nrf2 antioxidant signaling pathway in mice

Abstract: Proposed renoprotection mechanism of LYC via enhancing renal antioxidant in AFB1-treated mice kidney. The → indicates activation or induction, and ⊣ indicates inhibition or blockade.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 58 publications
3
29
0
Order By: Relevance
“…GSH-Px, SOD, CAT, and T-AOC are critical indicators for evaluating the capacity of the cellular antioxidant defense system [32,33]. An imbalance in oxidative stress defense leads to insufficient antioxidant responses and lipid peroxidation to generate MDA [31,34]. As mentioned, SCHPs-F1 increased the antioxidant defense parameters GSH-Px, SOD, CAT, and T-AOC and decreased levels of the lipid peroxidation marker MDA, thereby potentially alleviating oxidative stress of CTX-exposed kidneys.…”
Section: Discussionmentioning
confidence: 99%
“…GSH-Px, SOD, CAT, and T-AOC are critical indicators for evaluating the capacity of the cellular antioxidant defense system [32,33]. An imbalance in oxidative stress defense leads to insufficient antioxidant responses and lipid peroxidation to generate MDA [31,34]. As mentioned, SCHPs-F1 increased the antioxidant defense parameters GSH-Px, SOD, CAT, and T-AOC and decreased levels of the lipid peroxidation marker MDA, thereby potentially alleviating oxidative stress of CTX-exposed kidneys.…”
Section: Discussionmentioning
confidence: 99%
“…These results agree with the results of Abbas et al [36] who reported that lycopene ameliorates atrazine-induced oxidative damage in the adrenal cortex of male rats by activation of the RF/HO-1 pathway. Furthermore, Yu et al [37] reported that lycopene attenuates aflatoxin B1-induced renal injury with the activation of the RF antioxidant signaling pathway in mice. Therefore, it is highly suggested that lycopene-induced upregulation of antioxidant enzymes is mechanistically via activation of the RF pathway.…”
Section: Resultsmentioning
confidence: 99%
“…Each sample was analyzed in triplicates and the mRNA expression of the target genes was analyzed by 2 −△△Ct method, following normalization with β-actin gene. Primer sequences of HDAC1 and β-actin genes are shown as follows: HDAC1, 5’-TGAAGCCTCACCGAATCCG-3’ and 5’-GGGCGAATAGAACGCAGGA-3’ ( Deng et al, 2020 ); β-actin, 5’-GTTGGAGCAAACATCCCCCA-3’ and 5’-ACGCGACCATCCTCCTC TTA-3’ ( Yu et al, 2018 ).…”
Section: Methodsmentioning
confidence: 99%